Self-Efficacy, Work-Family Conflict, Work-Life Balance, and Workload on the Performance of KPP Pratama Karanganyar Employees in the Pandemic of Covid 19 - Taryono, Taryono; Mursito, Bambang; Aryati, Ida (Jurnal Ilmiah Sumber Daya Manusia, 2023)
This study aimed to determine the effect of self-efficacy, work-family conflict, work-life balance, and workload on the performance of KPP Pratama Karanganyar employees. This study uses quantitative methods with survey research. The population in this study were all KPP Pratama Karanganyar employees, namely 122 people. The research sample was the entire population of 122 people or all KPP Pratama Karanganyar employees. The data analysis technique used is multiple linear regression. Based on the research and discussion results, the F test shows that self-efficacy, work-family conflict, work-life balance, and workload simultaneously influence employee performance at KPP Pratama Karanganyar. The Adjusted R Square (R2) value is 0.564 or 56.4%. This means that 56.4% of the variables selected/entered into the model are correct, namely the variance of self-efficacy, work-family conflict, work-life balance, and workload can explain the employee performance variable of 56.4%, while the remaining 43.6% influenced by other variables such as work culture, work discipline, remuneration, and leadership style.